Evaluation of contact angle and mechanical properties of resin monomei filled with graphene oxide nanofibers - Campos Velo, Marilia Mattar de Amoedo [UNESP]; Nascimento, Tatiana Rita de Lima; Obeid, Alyssa Teixeira; Brondino, Nair Cristina Margarido [UNESP]; Mondelli, Rafael Francisco Lia (FapUNIFESP (SciELO), 2023)
This in vitro study synthesized hybrid nanofibers embedded in graphene oxide (GO) and incorporated them into experimental resin composite monomers to evaluate their physical-mechanical properties. Inorganic-organic hybrid nanofibers were produced with precursor solutions of 1% wt. GO-filled Poly (d,l-lactide, PLA) fibers and scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) characterized the morphology and chemical composition of the spun fibers. Resin composite monomers were developed and a total of 5°/o nanofibers were incorporated into the experimental materials. Three groups were developed: G1 (control resin monomers), G2 (resin monomers/PLA nanofibers), and G3 (resin monomers/inorganic-organic hybrid nanofibers). Contact angle (n=3), flexural strength (n=22), elastic modulus (n=22), and Knoop hardness (n=6) were evaluated. The mean of the three indentations was obtained for each sample. The normality of data was assessed by QQ Plot with simulated envelopes and analyzed by Welch's method (p<0.05). Overall, SEM images showed the regular shape of nanofibers but were non-aligned. Compositional analysis from EDS (n=6) revealed the presence of carbon and oxygen (present in GO composition) and Si from the functionalization process. The results of contact angle (°) and hardness (Kg/mm2) for each group were as follow, respectively: G1 (59.65±2.90; 37.48±1.86a), G2 (67.99±3.93; 50.56±1.03b) and G3 (62.52±7.40; 67.83±1.01c). The group G3 showed the highest Knoop hardness values (67.83 kg/mm2), and the flexural strength of all groups was adversely affected. The experimental resin composite composed of hybrid nanofibers with GO presented increased hardness values and hydrophilic behavior.
Keywords: biomaterials; graphene oxide; hybrids; nanofibers; resin composite